2000
DOI: 10.1016/s0013-7952(00)00022-3
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation and cracking behavior of three compacted landfill liner soils

Abstract: Tests were conducted to investigate desiccation cracking of three compacted liner soils obtained from local landfills in southeast Michigan. The soils had low plasticity with varying fines content. Large-scale samples of the soils were subjected to wetting and drying cycles. Surficial dimensions of cracks and suction in the soils were monitored. Surficial dimensions of cracks were quantified using the crack intensity factor (CIF), which is the ratio of the surface area of cracks to the total surface area of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(138 citation statements)
references
References 9 publications
8
116
0
1
Order By: Relevance
“…However, upon further drying the rate of CA increase started to decline and gradually reached stabilization on day 7. This observation is consistent with earlier studies on desiccation cracking behavior of polypropylene fiber-reinforced clayey soil [19] [22]. This stabilization in crack area was approximated as the intersection between the log of crack area and soil moisture content lines.…”
Section: Cracks In Soilsupporting
confidence: 91%
See 1 more Smart Citation
“…However, upon further drying the rate of CA increase started to decline and gradually reached stabilization on day 7. This observation is consistent with earlier studies on desiccation cracking behavior of polypropylene fiber-reinforced clayey soil [19] [22]. This stabilization in crack area was approximated as the intersection between the log of crack area and soil moisture content lines.…”
Section: Cracks In Soilsupporting
confidence: 91%
“…Our study also showed that, estimating the CIF from thinned binary images through the pixel count as well as the Cover/Brightness generated by the software were adequate and showed similar decomposition over time, although with an order of magnitude of 1 -2 between them. The SMCs that enhanced initiation, rapid propagation and development of cracks during the first 1 - 4 days are herein referred to as critical soil moisture contents analogous to the critical suctions employed by [22]. As aforementioned, the Crack Intensity Factor (CIF) of a digitized binary image was determined and expressed as the ratio of the surface area of the cracks to the total surface area of the binary image of the soil specimen.…”
Section: Cracks In Soilmentioning
confidence: 99%
“…The treatment mechanics and efficiency are less affected by these factors, as are their planted counterparts. However, the alterations of soil particles such as desiccation and creaking are reported to cause failures to the clay liner in landfills [7]. Therefore, the application of a compacted clay layer as the primary pollutant filter bed in non-planted CWs might experience the same issue.…”
Section: Introductionmentioning
confidence: 99%
“…Crack usually initiated and propagate in fine-grained materials including clayey soils [16] , gels [19], fine-grained mining wastes or tailings [18]. Yesiller et al, (2000) proposed that "large amount of cracking were always observed in samples with high fine contents and high suction in soils, and less cracking in soil with low fines content" [23]. It is obvious that porous materials with finer particles have smaller pore size.…”
Section: Influence Of Particle Sizementioning
confidence: 99%